The impact of endoscopic ultrasound on the management and outcome of patients with oesophageal cancer: an update of a systematic review. Issue 5 (May 2022) - Foley, K.G.; Franklin, J.; Jones, C.M.; Coles, B.; Roberts, S.A.; Underwood, T.J.; Crosby, T.
Abstract : AIM: To provide an updated systematic review concerning the impact of endoscopic ultrasound (EUS) in the modern era of oesophageal cancer staging. MATERIALS AND METHODS: To update the previous systematic review, databases including MEDLINE and EMBASE were searched and studies published from 2005 onwards were selected. Studies reporting primary data in patients with oesophageal or gastro-oesophageal junction cancer who underwent radiological staging and treatment, regardless of intent, were included. The primary outcome was the reported change in management after EUS. Secondary outcomes were recurrence rate and overall survival. Two reviewers extracted data from included articles. This study was registered with PROSPERO (CRD42021231852). RESULTS: Eighteen studies with 11, 836 patients were included comprising 2, 805 patients (23.7%) who underwent EUS compared to 9, 031 (76.3%) without EUS examination. Reported change of management varied widely from 0% to 56%. When used, EUS fine-needle aspiration precluded curative treatment in 37.5%–71.4%. Overall survival improvements ranged between 121 and 639 days following EUS intervention compared to patients without EUS. Smaller effect sizes were observed in a randomised controlled trial, compared to larger differences reported in observational studies. CONCLUSION: Current evidence for the effectiveness of EUS in oesophageal cancer pathways is conflicting and of limited quality. In particular, the extent to which EUS adds value to contemporary cross-sectional imaging techniques is unclear and requires formal re-evaluation. Highlights: Oesophageal cancer staging relies on a multi-modality approach. EUS can be used for diagnosis, staging and treatment of oesophageal cancer. The role of EUS in oesophageal cancer has been questioned since PET-CT was adopted. This systematic review updates the latest evidence for EUS in oesophageal cancer. Few data exist that examine the impact of EUS on management and outcomes.